APLIKASI METODE DRILL GUNA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PERKALIAN SISWA KELAS II SD - Uke Viani; Muhammad Rizal Fauzi; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2021)
The background in this study is the low achievement and enthusiasm for mathematics in elementary school. The study uses classroom action research methods by comparing the improvement in student learning outcomes before and after the drill method was applied. The study was conducted at SDN Cibeber 1 in the area of South Cimahi District, Cimahi City. The results of this study are student learning outcomes increased to 52.2% after the drill method was applied. Thus, it can be said that mathematics learning outcomes can improve due to the application of the Drill method to the multiplication material of students in grade II elementary school.